A Novel Technique of Aseptic Manufacture of Autologous Serum Eye Drops (ASEDs) and Sterility Analysis of the Bottled Ophtioles - Blaser, Frank; Meneau, Isabelle; Mihic-Probst, Daniela; Muth, Daniel Rudolf; Barthelmes, Daniel; Zweifel, Sandrine; Said, Sadiq; Bajka, Anahita (Klinische Monatsblätter für Augenheilkunde, 2024)
Purpose To introduce a novel technique of the aseptic manufacture of autologous serum eye drops (ASEDs) with a prefiltered closed system and to analyze the sterility of the produced ophtioles between 2018 and 2022.Methods This is a prospective single-center study conducted at the Department of Ophthalmology at a Swiss University Hospital between 2018 and 2022. For regulatory reasons, closed systems for manufacturing ASEDs are strongly recommended. We attached an upstream sterile filter (Sterivex PES0.22 µm Burlington, USA) to a commercially available closed system (COL System Modena, Italy) for manufacturing ASEDs. The goal of this novel approach was to reduce the microbiological contamination of the donated autologous blood. Using the presented manufacturing method, we are able to produce, on average, 56 ophtioles per batch, containing either 1.45 mL or 2.5 mL of autologous serum per ophtiole. For each batch of ASEDs, we performed a microbiological analysis by automated blood culture testing (BACTEC). This system examines the presence of bacteria and fungi.Results We analyzed all manufactured batches between 2018 and 2022. None of the 2297 batches and the resulting 129 060 ophtioles showed bacterial or mycotic contamination. During the analyzed period, two batches were discarded: one due to fibrin-lipid aggregations, further microbiological and histological work-up excluded any contamination; another due to false-positive HIV in serological testing. Overall, the contamination rate was 0%, and the batch discharge rate was 0.09%.Conclusions The combination of upstream sterile filtration with a commercial closed system for manufacturing ASEDs proved to be effective in ensuring sterility without any contamination over the past 4 years. This is becoming crucial, as the demand for autologous blood products for treating ocular surface disorders, such as refractory dry eyes or nonhealing defects of the corneal epithelium, is on the rise.
Keywords: autologous serum eye drops; ophtioles; sterility; contamination; closed system